Original paperA novel perineal shield for low-dose-rate prostate brachytherapy - Weiner, Joseph P.; Schwartz, David; Safdieh, Joseph; Polubarov, Alex; Telivala, Tejas; Worth, Matthew; Schreiber, David (Journal of Contemporary Brachytherapy, 2015)
Purpose: To study the impact on radiation exposure to staff through the use of an original perineal shield during low-dose-rate prostate brachytherapy. Material and methods: We designed a 1 mm thick stainless steel shield that duplicates and is able to slide directly over a standard commercialized prostate brachytherapy grid. We then analyzed the post-procedure exposure in 15 consecutive patients who underwent Iodine-125 seed placement. Measurements were performed with and without the shield in place at fixed locations relative to the grid template. Endpoints were analyzed using the paired two-sample t-test, with statistical significance defined as a p-value < 0.05. Results: The exposure at the midline grid template ranged from 0.144-0.768 mSv/hr without the shield, and 0.038-0.144 mSv/hr with the shield (p < 0.0001). The exposure 10 cm left of the grid template was 0.134-0.576 mSv/hr without the shield, and 0.001-0.012 mSv/hr with the shield (p < 0.0001). The exposure 10 cm right of the grid template was 0.125-0.576 mSv/hr without the shield, and 0.001-0.012 mSv/hr with the shield (p < 0.0001). The median reduction of exposure at the grid was 76% midline, 98.5% left, and 99% right. Similarly, each individual dose rate was recorded at 25 cm from the perineum, both with and without shield. The median reduction of exposure 25 cm from the perineum was 73.7% midline, 77.7% left and 81.6% right (p < 0.0001). Conclusions: Our novel shield took seconds to install and was non-restrictive during the procedure, and provided at least a four-fold reduction in radiation exposure to the brachytherapist.